Trimethyl 4,6-Dicyano-5-hydroxybenzene-1,2,3-tricarboxylate - Zonouzi, Afsaneh; Mirzazadeh, Roghieh; Ng, Seik Weng (MDPI, 2012)
A novel synthesis of a fully substituted fluorescent phenol by a one-pot reaction of dimethyl acetylendicarboxylate and malononitrile in the presence of catalysts has been developed. The structure of the synthesized compound was assigned on the basis of its elemental analysis, 1H-NMR, 13C-NMR, IR, mass spectral and X-ray data. The photophysical data of the new compound are reported. © 2012 by the authors; licensee MDPI, Basel, Switzerland.